2019
DOI: 10.1016/j.sleh.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Television use and its effects on sleep in early childhood

Abstract: Objectives: The purpose of this study was to investigate the impacts of television (TV) viewing and bedroom TV presence on young children's sleep as measured by actigraphy. Design: Analyses of covariance were run to examine differences in sleep duration and quality among children based on the presence of TVs in their bedrooms and the amount of TV watched. Setting: Recruited in preschools in Massachusetts; recorded ambulatory (in home, environs). Participants: Participants were 470 children between 33 and 71 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…The majority of studies (23/24) narrated a positive association between screen time and sleep problems [ 19 , 25 , 26 , 27 , 29 , 56 , 70 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Children being exposed to screen media use had a higher likelihood of having sleeping problems.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (23/24) narrated a positive association between screen time and sleep problems [ 19 , 25 , 26 , 27 , 29 , 56 , 70 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Children being exposed to screen media use had a higher likelihood of having sleeping problems.…”
Section: Resultsmentioning
confidence: 99%
“…also reported a significant association between television watching time and shortened sleep duration in early childhood 33 . Another study found that children with a television in their bedroom had shorter sleep duration than children with no television in their bedroom 34 …”
Section: Discussionmentioning
confidence: 91%
“…33 Another study found that children with a television in their bedroom had shorter sleep duration than children with no television in their bedroom. 34 In terms of birth abnormalities, birth trauma often causes circadian rhythm disorders in children with severe motor and intellectual disabilities, resulting in sleep disorders. 35 Mothers are also reported to feel stress more strongly than fathers when their infants have a sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not control for screen time in our models, which may act as a confounder in the relationship between 24-h movement behaviors and sleep quality. However, we have separately reported the impact of television on sleep in this population [ 62 ]. Finally, as these analyses were cross-sectional, causal relationships cannot be inferred.…”
Section: Discussionmentioning
confidence: 99%